Two Lysin-Motif Receptor Kinases, Gh-LYK1 and Gh-LYK2, Contribute to Resistance against Verticillium wilt in Upland Cotton - Gu, Zhouhang; Liu, Tingli; Ding, Bo; Li, Fangfang; Wang, Qian; Qian, Shasha; Ye, Fei; Chen, Tianzi; Yang, Yuwen; Wang, Jinyan; Wang, Guoliang; Zhang, Baolong; et al. (Frontiers in Plant Science, 2017)
Lysin-motif (LysM) receptor kinases (LYKs) play essential roles in recognition of chitin and activation of defense responses against pathogenic fungi in model plants Arabidopsis and rice. The function of LYKs in non-model plants remains elusive. In present work, we found that the transcription of two LYKs from cotton, Gh-LYK1 and Gh-LYK2, were induced after Verticillium dahliae (V. dahliae) infection. VIGS based silencing of Gh-LYK1 and Gh-LYK2 in cotton plants showed compromises resistance to V. dahliae. As putative pattern recognition receptors, both Gh-LYK1 and Gh-LYK2 are membrane localized and all three LysM domains of Gh-LYK1 and Gh-LYK2 are required for their chitin-binding ability. However, the findings that Gh-LYK2 is a psuedo-kinase and the ectodomain (ED) of Gh-LYK2 can induce reactive oxygen species burst in plant suggest Gh-LYK2 and Gh-LYK1 contribute differently to cotton defense. Taken together, our results established that both Gh-LYK1 and Gh-LYK12 are required for defense against V. dahliae in cotton and unravel that Gh-LYK2-ED plays a pivotal role in plant cell-death regulation.